Optimization of microbial DNA extraction in 96-format from fecal samples for Next Generation Sequencing - Tomnikov, Natalie (My University, 2022)
Gut microbiota composition is often determined by using Next Generation Sequencing methods. The demand for rapid, efficient, and reliable microbial profiling is continuously increasing, thus making the optimization of high-throughput 96-format DNA extraction integral for downstream applications. In this study, we analyzed the impact of four pre-treatment methods to the DNA extraction and 16S metabarcoding results. More specifically, pre-treatments with and without bead-beating were compared. Fecal DNA was extracted from infant, adult and senior fecal samples. The extraction also included negative controls and ZymoBIOMICS Gut Microbiome Standards to test the resolution of the sequencing target and assess DNA yield. The optimized kit was DNA Stool 200 Kit special H96 with Chemagic MSM I extraction robot. Four pre-treatments, including bead-beating and chemical lysis, were applied to the samples to assess the impact of the sample lysis and homogenization. The microbial composition was determined using 16S sequencing targeting V3V4 and V4 regions with Illumina Miseq platform. The observed compositions of the Gut Microbiome Standards differed considerably from the expected theoretical compositions with all methods and sequencing targets. The fecal samples showed different degrees of microbial diversity across different pre-treatment groups; however, the inclusion of bead-beating generally lead to higher degrees of microbial diversity. The extraction in 96-format proved to be? feasible. As the DNA extraction methods are advancing, it is important to validate new procedures with the existing NGS-methods. The application of 96-format could reduce the hands-on time as well as human error in clinical microbiology. The 96-format extraction systems proved to be suitable for fecal DNA extraction. However, the results indicate the need of a standardized methods for microbial profiling.

Suoliston mikrobikoostumuksen selvittämiseksi käytetään usein uuden sukupolven sekvensointimenetelmiä (engl. NGS). Korkean kapasiteetin 96-formaatissa olevan DNA-eristyksen optimoiminen alavirran sovelluksille on tärkeää, sillä kysyntä nopealle, tehokkaalle ja luotettavalle mikrobiologiselle profiloinnille on alati kasvamassa. Tässä tutkimuksessa analysoimme neljän esikäsittelytavan vaikutusta DNA-eristys -ja 16S viivakoodaustuloksiin. Tarkemmin sanottuna esikäsittelyjä ilman -ja helmiravistelun kanssa vertailtiin. Uloste-DNA:ta eristettiin aikuisen, vauvan ja seniorin ulostenäytteistä. Eristykseen kuului myös negatiivisia kontrolleja sekä ZymoBIOMICS Gut Standard -standardi sekvensointimenetelmän tarkkuuden testaamiseksi ja DNA:n saannon arvioimiseksi. Optimoitu kitti oli DNA Stool 200 Kit special H96 ja eristysrobotti Chemagic MSM I. Lyysiksen ja homogenisoinnin vaikutuksen tutkimiseksi näytteille tehtiin neljä eri esikäsittelyä, jotka sisälsivät kemiallisen -ja helmiravistelulyysiksen (engl. bead-beating). Mikrobikoostumus selvitettiin sekvensoimalla 16S-ribosomin V3V4 -ja V4-alueet käyttämällä Illumina Miseq-alustaa. Havaitut Gut Standard -standardien mikrobikoostumukset erosivat huomattavasti odotetuista teoreettisista koostumuksista kaikkien esikäsittelyjen ja sekvensointikohteiden suhteen. Eri esikäsittelymenetelmät tuottivat ulostenäytteille vaihtelevia diversiteettejä. Kuitenkin helmikäsittelyn sisällyttäminen johti yleensä korkeimpiin diversiteettilukuihin. DNA:n eristys 96-formaatissa todettiin mahdolliseksi On tärkeää validoida uusia menetelmiä vanhojen toimintatapojen valossa, koska DNA eristysmenetelmät kehittyvät. 96-formaatin käyttöönottaminen voisi vähentää käytännön työaikaa sekä ihmisestä johtuvia virhelähteitä kliinisen mikrobiologian alalla. Tämä 96- formaatti todettiin toteutettavissa olevaksi ulostenäytteiden DNA-eristyksessä. Kuitenkin tulokset viittaavat siihen, että standardisoituja menetelmiä tarvitaan mikrobikoostumuksen selvittämisessä.
Keywords: optimization, next generation sequencing, 16S, gut microbiome, dna extraction, feces